Projecting the Roles of the Indonesian State Revenue Authority toward Tax Administration's Performance - Hapsari, Nidya; Putra, Adhy Kusuma (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2025)
This study analyzes the impact of the Indonesian State Revenue Authority (SRA) on tax ratio and/or tax administration performance. The upcoming establishment of SRA, which is projected to take the semi-autonomous form under the direct command of the President, is part of tax reform in Indonesia. Using interpretive analysis and comparative research methods, the study finds that the idea of merging the Directorate General of Taxes, Directorate General of Customs and Excise, and Directorate of Non-Tax State Revenue into the SRA may contribute positively to increased state revenue and tax administration performance in Indonesia, which fiscal system is characterized by a high reliance on tax revenue to fund government expenditure and maintain economic stability. First, personnel and managerial autonomy gain perceptions of fairness and competence among taxpayers, thereby positively impacting the credibility of the tax authority. Second, state revenue affairs deserve a ministry-level organizational structure, and the 1945 Constitution of Indonesia binds the mandate. Third, the collection-function centralization on taxes (and other similar-character levies or social contributions) will reduce calculation gaps due to different definition standards. Fourth, it expands the opportunity for professional-based, transparent, and accountable judgment. Fifth, personnel, financial, and operational policy autonomy will improve tax administration operations and increase personnel work motivation and flexibility. However, the government needs to adopt the integrated semi-autonomous model gradually, continue improving the core governance of the revenue administration, assign the highest leadership positions to experienced professionals, and utilize digital technology to facilitate seamless coordination between revenue and expenditure functions.